The Learning Styles Neuromyth Is Still Thriving in Medical Education - Newton, Philip M.; Najabat-Lattif, Hannah Farukh; Santiago, Gabriella; Salvi, Atharva (Frontiers in Human Neuroscience, 2021)
Learning Styles theory promises improved academic performance based on the identification of a personal, sensory preference for informational processing. This promise is not supported by evidence, and is in contrast to our current understanding of the neuroscience of learning. Despite this lack of evidence, it appears that belief in the Learning Styles ‘neuromyth’ remains high amongst educators. ‘ We found that the use of Learning Style frameworks persist in education research for the health professions; 91% of 112 recent research papers published on Learning Styles are based upon the premise that Learning Styles are a useful approach to education. This is in sharp contrast to the fundamental principle of evidence-based practice within these professions. Here we offer perspectives from both research and student about this apparent mismatch between educational practice and clinical practice, along with recommendations and considerations for the future.